1985
DOI: 10.1093/infdis/152.6.1317
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Arachidonic Acid by Microfilariae of Brugia malayi

Abstract: To initiate studies on the significance of filarial arachidonic acid metabolism in the immunopathogenesis of human filariasis, we evaluated the ability of microfilariae of the human filarial parasite Brugia malayi to take up and incorporate exogenous arachidonate. When 4 X 10(5) microfilariae were incubated in vitro with 3 nM [3H]arachidonic acid for 0.2, 24, and 48 hr, 23%, 70%, and 75% of tritium activity were associated with microfilariae, respectively. [3H]arachidonic acid was taken up by viable but not by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…A key observation which pinpoints eicosanoids as central players in filarial infection is that microfilariae themselves secrete prostanoids, in particular prostacyclin and PGE2 (Liu, Serhan & Weller, 1990). Earlier studies had established that Mf incorporate exogenous arachidonic acid (Longworth et al 1985). When Mf were tested in the presence of DEC, parasite prostanoid production was severely inhibited (Kanesa-thasan et al 1991).…”
Section: Dec Effects On Arachidonic Acid Metabolism May Be the Primarmentioning
confidence: 99%
“…A key observation which pinpoints eicosanoids as central players in filarial infection is that microfilariae themselves secrete prostanoids, in particular prostacyclin and PGE2 (Liu, Serhan & Weller, 1990). Earlier studies had established that Mf incorporate exogenous arachidonic acid (Longworth et al 1985). When Mf were tested in the presence of DEC, parasite prostanoid production was severely inhibited (Kanesa-thasan et al 1991).…”
Section: Dec Effects On Arachidonic Acid Metabolism May Be the Primarmentioning
confidence: 99%
“…Most parasitic helminths lack the ability to synthesize polyunsaturated fatty acids de novo (Frayha & Smyth, 1983). In microfilariae and adults of Brugia malayi , arachidonate is rapidly esterified and incorporated into phospholipids and neutral lipids (Longworth et al , 1985, 1987, 1988; Liu & Weller, 1990). In the presence of exogenous arachidonic acid, Taenia taeniaformis metacestodes may generate thromboxane (Leid & McConnell, 1983a), prostaglandins (Leid & McConnell, 1983b) and hydroxyeicosatetraenoic acid (HETE)-like compounds with chemotactic activities towards eosinophils (Potter & Leid, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the thromboxanes (Txs) constrict blood vessels, suppress cyclic AMP, and promote platelet aggregation, while leukotrienes (LTs) are related to vascular permeability, chemotaxis, and polymorphonuclear leukocyte activation (17). Some of these lipid mediators have been observed in lymphatic filariae (10,11,13) and Onchocerca volvulus (4). Clinical studies have demonstrated high concentrations of TxB2 in the plasma of patients with septic and endotoxic shock (1) and in patients with chronic obstructive pulmonary disease (6).…”
mentioning
confidence: 99%